Remaining Service Life Struktur Conveyor B pada Tambang Batubara PT XYZ di Kabupaten Kotabaru, Provinsi Kalimantan Selatan - Rizky Ade Pradana; Elfida Moralista; Zaenal (UNISBA Press, 2022)
Abstract. Conveyor structure is a means of transportation used in the coal mining industry to assist the transfer of minerals. The conveyor structure is made of carbon steel which is subject to corrosion. Corrosion will cause the conveyor structure to decrease in thickness. Therefore, it is necessary to control and monitor corrosion on the conveyor structure. The purpose of this study is to determine the type of corrosion, the corrosion control applied to the conveyor structure. The methodology used in this study is the thickness of the conveyor structure. Measurements were made using the Ultrasonic Thickness Gauge TT 130 on a 90 meter long conveyor structure with 3 segments and 25 test points. Environmental conditions in the 2015-2019 period have an average rainfall of 197.98 mm/year, an average air temperature of 26.91oC and an air humidity of 83.62%. The type of corrosion that occurs in the conveyor structure is uniform corrosion. In the identification of corrosion, the use of a 3-layer coating method, namely the primer coating using Seaguard 5000, Intermediate coating Sherglass FF, and Top coating using aliphatic acrylic modified polyurethane. Abstrak. Struktur conveyor adalah alat angkut yang digunakan pada industri pertambangan batubara untuk menunjang pemindahan material bahan galian. Struktur conveyor terbuat dari baja karbon yang dapat mengalami korosi. Korosi akan menyebabkan struktur conveyor mengalami pengurangan ketebalan. Oleh karena itu, maka diperlukana pengendalian dan monitoring korosi pada struktur conveyor. Tujuan dilakukannya penelitian ini yaitu mengetahui jenis korosi, metode pengendalian korosi yang diaplikasikan pada stuktur conveyor. Metodologi yang digunakan dalam penelitian ini yaitu pengukuran ketebalan struktur conveyor. Pengukuran dilakukan menggunakan alat Ultrasonic Thickness Gauge TT 130 pada struktur conveyor sepanjang 90 meter dengan 3 segmen dan 25 test point. Kondisi lingkungan dalam rentang waktu 2015-2019 memiliki curah hujan rata-rata 197,98 mm/tahun, temperature udara rata-rata 26,91oC dan kelembapan udara 83,62%. Jenis korosi ytang terjadi pada struktur conveyor yaitu korosi merata. Dalam pengenalian korosi digunakan metode coating 3 lapis yaitu primer coating menggunakan Seaguard 5000, Intermediate coating Sherglass FF, dan Top coating menggunakan aliphatic acrylic modified polyurethane.